Stroke masks – a case report - Chmielewska, Beata; Leksa, Natalia; Aebisher, David; Galiniak, Sabina; Leksa, Dawid; Bartosz, Seweryn; Bartusik-Aebisher, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Stroke is a common vascular disease encountered in the work of a practitioner. Despite this, his differentiation is difficult. This is due to a variety of diseases that can be a “mask” for stroke. These are neurological diseases other than vascular (brain tumors, epilepsy), head injuries and a number of metabolic disorders (fluctuations in glucose, electrolytes). Aim. This work aims to approximate the differentiation of this common disease entity. Case reports show both clinical view and diagnostic difficulties. Description of the cases. Case 1. The patient 59 years old treated for bipolar disorder, hypertension and alcohol abuse. Case 2. The patient 68 years old treated for type 2 diabetes, hypertension, ischemic heart disease, cholecystolithiasis – cholecystectomy. Conclusion. Stroke is a significant clinical and social problem both in Poland and in the world. Despite this, its diagnostics and especially differentiation is difficult. When analyzing the case of each patient with suspected sudden CNS vascular disease, all of them should be remembered. It should also be borne in mind that differential diagnosis cannot delay specific treatment for stroke.
Keywords: brain metabolic disorders; MRI; stroke